Impact of different temperature abuse scenarios on sensory quality and off‐odour formation in ready‐to‐eat salad leaves. (9th November 2020) - Raffo, Antonio; Senatore, Massimo; Moneta, Elisabetta; Paoletti, Flavio; Peparaio, Marina; Saggia Civitelli, Eleonora
Summary: Packages of ready‐to‐eat (RTE) wild rocket and lettuce baby leaves were subjected during 8 days of cold storage to a chronic temperature abuse (CTA) at sub‐optimal storage temperature (10 °C) or to a short‐term (6 h) abuse at ambient temperature (STA) to evaluate the impact of two temperature abuse scenarios on gas composition within the packages, leaf sensory quality and volatile organic compounds (VOCs). In both species, the CTA scenario had a markedly higher impact on gas composition, sensory quality and off‐odour formation than the STA, and the limit of sensory acceptability was reached in the CTA scenario 4 days or more earlier than in the STA. Sulphur compounds were the main responsible for off‐odour perception in both leafy salads. Results from the present study may be useful in the assessment of critical points in the cold chain of RTE fresh produce and in prioritising actions towards improved cold‐chain management. Abstract : Commercial produced packages of ready‐to‐eat wild rocket and lettuce baby leaves were subjected to two post‐packaging temperature abuse scenarios in a lab simulation. In both salad types, the chronic temperature abuse (CTA) scenario had a markedly higher adverse impact on sensory quality and off‐odour formation (as evaluated by volatile organic compounds analysis) than the short term abuse (STA). As a result, the limit of sensory acceptability was reached in the CTA scenario 4 days or more earlier than in the STA.